2008
DOI: 10.2118/118431-pa
|View full text |Cite
|
Sign up to set email alerts
|

Seawater in Chalk: An EOR and Compaction Fluid

Abstract: Summary North Sea chalk reservoirs are characterized as being purely biogenic and naturally fractured, having low matrix permeability and very high porosity (30 to 45%). The reservoir temperature is usually high, more than 90°C, and the wetting conditions appear to be moderately water-wet to neutral. Even though the permeability contrast between the matrix and fractures is significant, the injection of seawater has been a great success with the Ekofisk field as an example (estimated oil recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 17 publications
2
62
0
Order By: Relevance
“…Austad research group proposed the Multicomponent Ionic Exchange (MIE) theory for carbonate rocks [16][17][18][19][20][21][22][23]. The main role proposed for sulfate which adsorbs onto the positively charged calcite surface and reduces the positive surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…Austad research group proposed the Multicomponent Ionic Exchange (MIE) theory for carbonate rocks [16][17][18][19][20][21][22][23]. The main role proposed for sulfate which adsorbs onto the positively charged calcite surface and reduces the positive surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the world's remaining oil reserves are located in formations, for example, mixedwet to oil-wet fractured carbonate reservoirs, that require enhanced oil recovery techniques (EOR), such as water-alternating-gas (WAG) (Christensen et al 2001), chemical injection (Austad et al 2008) and thermal recovery (Al-Hadhrami and Blunt 2001). Such EOR techniques can lead to large three-phase flow regions and modify the wettability of the porous media locally.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that seawater can favorably affect oil/brine/rock interactions to alter wettability and eventually improve waterflood recoveries in chalk (pure calcium carbonate rock) based on spontaneous imbibition tests (Austad et al, 2005;Strand et al, 2006;Zhang and Austad, 2006;Zhang et al, 2007;Austad et al, 2008). These studies attributed the resulting improved oil recoveries to wettability alteration caused by the interplay of potential determining ions present in the seawater, mainly (SO 4 ) 2-, Ca 2ϩ , and Mg 2ϩ .…”
Section: Introductionmentioning
confidence: 98%